2011
DOI: 10.1179/1743284711y.0000000019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between microstructure and deformation behaviour during dynamic compression in Ti–3Al–5Mo–5V alloy

Abstract: The relationship between microstructure and deformation and damage behaviour during dynamic compression in Ti-3Al-5Mo-5V alloy has been studied using several experimental techniques, including optical microscopy, scanning electron microscopy and microhardness measurements. It was found that the deformation behaviour during dynamic compression was closely related to deformation parameters. After dynamic deformation, the deformation shear band that formed in the titanium alloy had microhardness similar to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
3
1
Order By: Relevance
“…During the study of microstructure, shear bands observed in Refs. [16,25] were not obviously found in our paper. Several facts can account for this difference.…”
Section: Microstructure Evolution With Different Tmp Parameterscontrasting
confidence: 58%
See 1 more Smart Citation
“…During the study of microstructure, shear bands observed in Refs. [16,25] were not obviously found in our paper. Several facts can account for this difference.…”
Section: Microstructure Evolution With Different Tmp Parameterscontrasting
confidence: 58%
“…Several facts can account for this difference. Dynamic compression experiments were conducted at much higher temperature (above 950 • C) and smaller deformation rate (0.001-1 s −1 ) in our study compared with the low room temperature and high deformation rate (100-500 mm/s) in [16,25]. The deformation heating resulting from low thermal conductivity of titanium and high compression rate contributed to this kind of localized deformation bands [18].…”
Section: Microstructure Evolution With Different Tmp Parametersmentioning
confidence: 89%
“…Up to now, many investigations mainly focused on this flow behavior by experiment, theory and simulation methods as well as the shear band models in alloys [33,[37][38][39][40][41][42]. Although previous approaches provided several valid models to describe the flow behavior of metallic glass or shear band model, the stressdependent plasticity has rarely been analyzed systematically [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…The effects of heat treatment temperature and time on the phase formation of the plate structure in the BT16 titanium alloy are studied. Recently, the relationship between microstructure and deformation behaviour during dynamic compression in this alloy has been studied, 19 but it does not contain the detailed measurements of microstructural changes induced by heat treatment.…”
Section: Introductionmentioning
confidence: 99%